2022
DOI: 10.1186/s12905-022-01923-7
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, pain, and health-related quality of life in gynecological patients undergoing surgery for benign and malignant conditions: a 12-month follow-up study

Abstract: Background Gynecological surgery has many impacts on women’s physical and mental health, and efforts to improve recovery from surgery are constantly under evaluation. Resilience is an ability to overcome stressors and adversities, such as traumas and surgeries. This study aimed to explore patients’ resilience and psychological symptoms in relation to recovery, health-related quality of life (HRQoL), and pain one year after gynecological surgery. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Furthermore, the experience of distress was statistically significant in the first phase of treatment. The qualitative description of insufficient emotional support confirms the quantitative findings of distress, and this result is in line with a Finnish study by Isokääntä et al (2022), who followed patients with gynaecological cancer for 12 months and examined the results of the HRQoL questionnaire. Distress worsened in the malignant cancer group during the follow-up period.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the experience of distress was statistically significant in the first phase of treatment. The qualitative description of insufficient emotional support confirms the quantitative findings of distress, and this result is in line with a Finnish study by Isokääntä et al (2022), who followed patients with gynaecological cancer for 12 months and examined the results of the HRQoL questionnaire. Distress worsened in the malignant cancer group during the follow-up period.…”
Section: Discussionsupporting
confidence: 88%
“…The respondent chooses the level that best describes her/his present health status from each dimension (15D©). This instrument can be used to assess the quality-of-life experience of a specific patient group and has been widely used in studies of cancer patients (Flyum et al, 2021;Isokääntä et al, 2022).…”
Section: The 15d Health-related Quality-of-life Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience has been specifically chosen over other tools for evaluating the psychological impact on outcomes as the ability to cope with stress is useful in the recovery and rehabilitation after surgery across many fields of medicine. 3 , 10 , 16 A recent study evaluating total knee arthroplasty (TKA) patients showed that preoperative resilience is an important predictor of physical and mental health of patients at 3 months and 12 months postsurgery. 16 Further, greater concurrent resilience was associated with better scores across all measured outcomes, which is in contrast to a recent study of TKA patients by Haffar et al 8 which found no significant correlation between resilience and patient-reported outcome scores, both measured 1 year postoperatively.…”
mentioning
confidence: 99%